How can Bitcoin Price Fluctuations be Explained? - KjÃ¦rland, Frode; Meland, Maria; Oust, Are; Ã˜yen, Vilde (International Journal of Economics and Financial Issues, 2018)
The purpose of this study is to uncover factors that explain Bitcoin’s price fluctuations. The price of the cryptocurrency Bitcoin is volatile and has increased from zero in 2009 to more than 19500 USD in December 2017. To explain the price movements we have estimated two Autoregressive Distributed Lag models by using Ordinary Least Squares regression. The data includes 279 weekly observations from 18.09.2011 to 05.02.2017 (before the extreme development from the summer of 2017). The dependent variable is the Bitcoin price and the analysis has examined nine independent variables. Our main finding and contribution is that political incidents and statements (“shocks”) are significant drivers of Bitcoin’s price. Moreover, the volume of Bitcoin and Bitcoin’s price has a significant, negative relationship. The interest of Bitcoin, measured by Google searches, has a positive, significant relationship with Bitcoin’s price. The study does not find evidence for Bitcoin being a safe haven investment. Keywords: Bitcoin, crypto currency, political incidents, price explanation JEL Classifications: C10, G15